Jawabanmu

2014-03-30T23:59:26+07:00
Jika kurang mengerti soalnya..mungkin di perjelas lagi
2014-03-31T07:47:07+07:00
f(x) = 3x - 1 
(f o g)(x) =  \frac{3 x^{2} - x - 3}{x+2}
maka g(x) =
?
(f o g)(x) =  \frac{3 x^{2} - x - 3}{x+2}
f (g(x)) =
 \frac{3 x^{2} - x - 3}{x+2}
3 (g(x) - 1 =  \frac{3 x^{2} - x - 3}{x+2}
3 (g(x)) = \frac{3 x^{2} - x - 3}{x+2} + 1
3 (g(x)) = \frac{3 x^{2} - x - 3}{x+2} +  \frac{x+2}{x+2}
3 (g(x)) = \frac{3 x^{2} - 1}{x+2}
   g(x)  = \frac{3 x^{2} - 1}{x+2} .  \frac{1}{3}
   g(x)  = \frac{3 x^{2} - 1}{3x+6}

semoga membantu :) jadikan yang terbaik ya :))